Modular wavemarker design for harbours and ships physical model testing - Eškinja, Zdravko (Array, 2008)
Summary: The paper presents design and implementation of a portable modular wavemaker system for producing regular and irregular waves in laboratory basins and fl umes. The system was built for the purpose of testing the impact of the sea waves on ships and coastal facilities. It is suitable for generation of all tipes regular and irregular surface waves. Modular system structure maintains high degree of fl exibility and reusability. Finally, the testing process on the physical model of Split harbour is described, and the currently obtained results are shown